The physical and chemical stability of cisplatin (Teva) in concentrate and diluted in sodium chloride 0.9% - Karbownik, Agnieszka; Szałek, Edyta; Urjasz, Hanna; Głęboka, Aleksandra; Mierzwa, Emilia; Grześkowiak, Edmund (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : The subject of study was the stability of cisplatin in concentrate in glass vials and diluted in polyethylene (PE) bags stored at 15–25°C for up to 30 days. Material and methods : Original vials of cisplatin injection (1 mg/ml, Teva) were stored at room temperature and subjected to re-piercing after 1, 2, 3, 7, 14, 21, 28 and 30 days following the initial piercing. Cisplatin infusions at nominal concentrations of 0.1 mg/ml were prepared in 0.9% sodium chloride (1000 ml) in PE bags. Chemical stability was measured by means of a stability-indicating high-performance liquid chromatography (HPLC) assay. Physical stability was assessed by visual inspection in normal light. Results : The concentration of cisplatin at each sampling time in the analysed solutions remained within 92.0–100.7% of initial concentration, regardless of the container. No changes in colour or turbidity were observed in any of the vials or prepared solutions. Conclusions : Cisplatin, both undiluted in glass containers and diluted with NaCl 0.9% in PE bags, remains stable (< 10% degradation) for at least 30 days at room temperature when protected from light.